Higher anxiety levels negatively correlated with of sleep quality persons with hemodialysis; A cross-sectional study - Wantonoro, Wantonoro; Uli, Rosmaida; Nguyen, Tuan Van (Edelweiss Applied Science and Technology, 2025)
Haemodialysis is the commonest form of kidney replacement therapy in the world. Physical deterioration and psychological such as anxiety is common problem in this therapy. In addition, quality of sleep is important for this vulnerable population. Nurses have an important role in reduce anxiety and increasing quality of sleep, however there is little known in Indonesian sample. To determine the correlation between anxiety level and sleep quality persons with haemodialysis. Quantitative research-cross-sectional study approach. Two hundred and thirty-four respondents participated in this study. The Pittsburgh Sleep Quality Questionnaire (PSQI) and The Hamilton Anxiety Rating Scale (HARS) Indonesia version questionnaires were administered in this study. Kendall Tau data analysis technique was used in this study. Significant correlation between anxiety and sleep quality in persons with haemodialysis (p=0.001; r=0.640). Higher anxiety levels negatively correlated with of sleep quality persons with haemodialysis. Managing anxiety could potentially improve the sleep quality of persons with haemodialysis. Assessment and, nursing intervention strategy for manage persons with haemodialysis’ anxiety level are needed. Identify the predictor factor of anxiety in this population are recommended for future work.